Implementation of Government Policies in Waste Management in South Dumai District, Dumai City - Dila Erlianti; Fitri Angraini; M. Khairul Sandi; Ria Maharani (Civiliza Publishing, 2026)
Waste management is one of the environmental problems that still often occur in urban areas, including in South Dumai District, Dumai City. This research aims to find out the implementation of government policies in waste management in South Dumai District, Dumai City and to find out the supporting and inhibiting factors in its implementation. This study uses a qualitative approach with a descriptive type of research. The research informants were determined purposively, consisting of employees of the Environmental Service, cleaners, and the public. Data collection techniques are carried out through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawn. The research analysis refers to the theory of policy implementation put forward by George Edward III in 1980 (Ravyansyah et al., 2022) with indicators that include communication, resources, disposition, and bureaucratic structure. The results of the study show that the implementation of waste management policies in South Dumai District has not been running optimally. The supporting factors are the commitment of the cleaning staff who are quite good and a clear division of duties between related parties. Meanwhile, the inhibiting factors include a lack of information to the public and limited number of officers, transport fleets, and temporary disposal facilities.